Becoming an effective mentoring leader proven strategies for building excellence in your organization - Rothwell, William (McGraw Hill, 2013)
Breaks down the essentials of mentoring, and shows you how to take advantage of this valuable new workplace dynamic. This title helps you learn: the smartest way to incorporate mentoring into your day-to-day leadership role; the fastest way to equip, inspire, and motivate your staff; and the differences between mentoring, coaching, and teaching.